Pengaruh musik suara alam terhadap tekanan darah - Lita; Heldiayana Ardianti; Meisa Daniati (Jurnal Kesehatan Komunitas, 2019)
Hypertension is also called the silent killer because it does not cause symptoms, but if left untreated will become a serious health problem. Hypertension can be caused by various factors. This study aims to identify risk factors of hypertension in Puskesmas Harapan Raya Pekanbaru. The design used in this study is a simple descriptive. The samples are 180 people with purposive sampling technique. Measuring instrument used is kesioner. The analysis used univariate analysis to determine the frequency distribution factor of hypertension that can not be changed and hypertension factors that can be changed. The results of the study of factors that can not be changed hypertension showed an average 40-year-old hypertensive patients, mostly female (51.1%), have descended hypertension (97.8%), from the tribe of Minang (40.6%) , Factors that can be changed hypertension showed smoking patients (37.2%), stressed (65%), obesity (22.8%) and had a history of diabetes (52%). From the results of the study are expected for health workers and families pay more attention to risk factors of hypertension and maximize treatment in cases of hypertension